Interpreting therapeutic landscape experiences through rural stroke survivors' biographies of disruption and flow. (April 2017) - Meijering, Louise; Lettinga, Ant T.; Nanninga, Christa S.; Milligan, Christine
Abstract: This article utilizes the concepts of biographical disruption and biographical flow to expand understandings of how a therapeutic engagement with the rural landscape may change over time for individual stroke survivors. In doing so, it explores how the rural landscape can be experienced as both a therapeutic and a non-therapeutic landscape. The paper draws on in-depth interviews with nineteen stroke survivors living in rural areas in the Northern Netherlands. Because of the cognitively and physically disabling changes that can occur as a result of stroke, interviewees' stories revealed complex and often contradictory experiences of the rural, post-stroke, that varied significantly from their pre-stroke experiences. Our findings demonstrate that the rural holds potential to function as a therapeutic landscape for stroke survivors, especially through its enabling natural and social characteristics. However, the different physical, social, natural, and healthcare aspects of the rural can also disrupt stroke survivors' individual biographies and their sense of self. The privileging of place in these biographies may provide important insights that can help improve the practice of stroke care. It also leads us to conclude that the concepts of biographical flow and disruption, though useful, need to take into account the influence of the wider (spatial) context. We thus coin the terms bio- geo -graphical flow and bio- geo -graphical disruption, and suggest that these may more accurately reflect the spatio-temporal disruptions and flows experienced by stroke survivors in the post-stroke period. Highlights: Bio- geo -graphical disruption and flow reflect the spatio-temporal dimension. Time and place effect rural stroke survivors' therapeutic landscape experiences. Stroke survivors struggle to move and live in 'ableist' rural spaces.